Causal network analysis of head and neck keloid tissue identifies potential master regulators. (18th March 2016) - Garcia‐Rodriguez, Laura; Jones, Lamont; Chen, Kang Mei; Datta, Indrani; Divine, George; Worsham, Maria J.
Abstract : Objectives/Hypothesis: To generate novel insights and hypotheses in keloid development from potential master regulators. Study Design: Prospective cohort. Methods: Six fresh keloid and six normal skin samples from 12 anonymous donors were used in a prospective cohort study. Genome‐wide profiling was done previously on the cohort using the Infinium HumanMethylation450 BeadChip (Illumina, San Diego, CA). The 190 statistically significant CpG islands between keloid and normal tissue mapped to 152 genes ( P < .05). The top 10 statistically significant genes ( VAMP5, ACTR3C, GALNT3, KCNAB2, LRRC61, SCML4, SYNGR1, TNS1, PLEKHG5, PPP1R13 ‐α, false discovery rate <.015) were uploaded into the Ingenuity Pathway Analysis software's Causal Network Analysis (QIAGEN, Redwood City, CA). To reflect expected gene expression direction in the context of methylation changes, the inverse of the methylation ratio from keloid versus normal tissue was used for the analysis. Causal Network Analysis identified disease‐specific master regulator molecules based on downstream differentially expressed keloid‐specific genes and expected directionality of expression (hypermethylated vs. hypomethylated). Results: Causal Network Analysis software identified four hierarchical networks that included four master regulators (pyroxamide, tributyrin, PRKG2, and PENK) and 19 intermediate regulators. Conclusions: Causal Network Analysis of differentiated methylated gene data of keloid versus normal skin demonstrated four causal networks with four master regulators. These hierarchical networks suggest potential driver roles for their downstream keloid gene targets in the pathogenesis of the keloid phenotype, likely triggered due to perturbation/injury to normal tissue. Level of Evidence: NA Laryngoscope, 126:E319–E324, 2016